Welcome :: Homework Help and Answers :: Mathskey.com
Welcome to Mathskey.com Question & Answers Community. Ask any math/science homework question and receive answers from other members of the community.

13,435 questions

17,804 answers

1,438 comments

130,374 users

Simplify questions

0 votes

Simplify questions

asked Oct 6, 2018 in ALGEBRA 2 by anonymous

1 Answer

0 votes

5)

1 / [8(a^3)b(c^5)]^-2   =   [8(a^3)b(c^5)]^2

                                  =   [8(a^3)b(c^5)]^2

                                  =   (8^2) (a^3)^2 b^2 (c^5)^2

                                  =   64 (a^6) b^2 (c^10)

7)

-3x^3(-3x^2)^2   =   -3x^3(-3)^2 (x^2)^2

                          =   -3x^3(9)x^4

                          =   -27x^(3+4)

                          =   -27x^7

8)

3^-1 + 3^-2   =   1/3 + 1/(3^2)

                    =   1/3 + 1/9

                    =   (3 + 1)/9

                    =   4/9

9)

[(a^2)(b^-3)(c^2) ] / [ (a^3)(b^-7)c]   =   [(b^-3)(c) ] / [ (a)(b^-7)]

                                                        =   [(b^-3)(b^7)(c) ] / (a)

                                                        =   [(b^-3+7(c) ] / (a)

                                                        =   cb^4 / a

Answer : 

5)   1 / [8(a^3)b(c^5)]^-2   =   64 (a^6) b^2 (c^10)

7)   -3x^3(-3x^2)^2   =   -27x^7

8)   3^-1 + 3^-2   =  4/9

9)   (a^2)(b^-3)(c^2) ] / [ (a^3)(b^-7)c]   =   cb^4 / a.

answered Oct 7, 2018 by homeworkhelp Mentor

Related questions

asked Oct 2, 2018 in ALGEBRA 2 by anonymous
asked Oct 13, 2018 in ALGEBRA 1 by anonymous
...